Visual Da‘wah in the Mediatized Era: A Virtual Ethnographic Analysis of Illustrative Content on the Instagram Account @sholahayub - Sirajuddin, Muhammad; Aniq Nahdia Lulu Annawawie; Hermansah, Tantan; Fanshoby, Muhammad (Jurnal Pewarta Indonesia, 2025)
This study examines digital Islamic preaching content on the Instagram account @sholahayub using the media space theory (Nasrullah, 2017) to revisit communication theory within the context of contemporary da’wah. The study assumes posits that visual content and user interactions on social media not only convey religious messages but also collectively shape religious identity and solidarity, particularly in humanitarian issues such as Palestine. The method employed is qualitative analysis based on cyber media analysis across four levels: media space, media document, media object, and user experience, with data consisting of illustrative posts, reflective narratives, and user responses. The findings reveal that semi-realistic illustrations and contemplative captions create a communicative and affective preaching space, where user interactions demonstrate deep emotional and spiritual engagement. These results expand communication theory by showing that social media functions as a dynamic, inclusive, and socially relevant space for the production of religious meaning. In conclusion, digital da’wah through Instagram serves as an effective medium of communication for fostering spiritual awareness, humanitarian solidarity, and strengthened devotion to Allah through transformative visual and emotional experiences.